Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Miao, Xin-Yu; Zhu, Xiao-Xiao; Gu, Zhao-Yan; Fu, Bo; Cui, Shao-Yuan; Zu, Yuan; Rong, Ling-Jun; Hu, Fan; Chen, Xiang-Mei; Gong, Yan-Ping; Li, Chun-Lin (Cell biochemistry and biophysics, 2022)
Vascular endothelial cells play a vital role in atherosclerotic changes and the progression of cardiovascular disease in older adults. Previous studies have indicated that Astragalus polysaccharides (APS), a main active component of the traditional Chinese medicine Astragalus , protect mitochondria and exert an antiaging effect in the mouse liver and brain. However, the effect of APS on rat aortic endothelial cell (RAEC) senescence and its underlying mechanism have not been investigated. In this study, we extracted RAECs from 2-month-old male Wistar rats by the tissue explant method and found that APS ameliorated the high-glucose-induced increase in the frequency of SA-β-Gal positivity and the levels of the senescence-related proteins p16, p21, and p53. APS increased the tube formation capacity of RAECs under high-glucose conditions. Moreover, APS enhanced the expression of the mitochondrial Na + /Ca 2+ exchanger NCLX, and knockdown of NCLX by small interfering RNA (siRNA) transfection suppressed the antiaging effect of APS under high-glucose conditions. Additionally, APS ameliorated RAEC mitochondrial dysfunction, including increasing ATP production, cytochrome C oxidase activity and the oxygen consumption rate (OCR), and inhibited high-glucose-induced NLRP3 inflammasome activation and IL-1β release, which were reversed by siNCLX. These results indicate that APS reduces high-glucose-induced inflammasome activation and ameliorates mitochondrial dysfunction and senescence in RAECs by modulating NCLX. Additionally, APS enhanced the levels of autophagy-related proteins (LC3B-II/I, Atg7) and increased the quantity of autophagic vacuoles under high-glucose conditions. Therefore, these data demonstrate that APS may reduce vascular endothelial cell inflammation and senescence through NCLX.